A Study on Education and the Organization of School Libraries in the Perspective of Total Quality Management - Cengiz Aslan (Türk Kütüphaneciliği)
The arrangement of enriched school libraries (Z Library) established by the Republic of Turkey Ministry of National Education are analyzed in the perspective of total quality management in terms of institutionalization and supervision, goals and productivity.